2013
DOI: 10.1038/srep01811
|View full text |Cite|
|
Sign up to set email alerts
|

Existence of G-quadruplex structures in promoter region of oncogenes confirmed by G-quadruplex DNA cross-linking strategy

Abstract: Existence of G-quadruplex DNA in vivo always attract widespread interest in the field of biology and biological chemistry. We reported our findings for the existence of G-quadruplex structures in promoter region of oncogenes confirmed by G-quadruplex DNA cross-linking strategy. Probes for selective G-quadruplex cross-linking was designed and synthesized that show high selectivity for G-quadruplex cross-linking. Further biological studies demonstrated its good inhibition activity against murine melanoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…The formation and stabilization of this structure are further dependent on the presence of a monovalent cation, especially potassium and sodium, which sits in a central channel between each pair of tetrads . DNA sequences that can form G‐quadruplexes are widely present in biologically relevant regions of genes contributing to genomic stability, control of replication, and gene expression . The first biologically relevant quadruplex forming sequences were discovered in eukaryotic chromosomal telomeric DNA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and stabilization of this structure are further dependent on the presence of a monovalent cation, especially potassium and sodium, which sits in a central channel between each pair of tetrads . DNA sequences that can form G‐quadruplexes are widely present in biologically relevant regions of genes contributing to genomic stability, control of replication, and gene expression . The first biologically relevant quadruplex forming sequences were discovered in eukaryotic chromosomal telomeric DNA .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 DNA sequences that can form G-quadruplexes are widely present in biologically relevant regions of genes contributing to genomic stability, control of replication, and gene expression. [3][4][5][6] The first biologically relevant quadruplex forming sequences were discovered in eukaryotic chromosomal telomeric DNA. 3,4,6 The telomere region contains d(TTAGGG) tandom sequences, which can fold spontaneously into G-quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the CD spectrum Pu27 G4 in the presence of complexes 1 – 3 suggested a mixture G-quadruplexes DNA of parallel and antiparallel G-quadruplex conformations, likely because 1 – 3 preferentially folded the Pu27 G4 DNA into a mixed-type or hybrid G4 structure in these experimental conditions5152. In all, it is clear that the parallel and antiparallel (mixed-type or hybrid G4 structure) conformation of the G4 DNA after treatment with 1 – 3 was favorable for the binding of Pu27 G4 in TBS, which also suggested that complexes 1 – 3 might interact with the loops and grooves of G-quadruplex DNA102433385152. In addition, in the presence of K + , the CD data indicated that HTG21, and Pu39 DNAs (sequence) exhibited a mixture G-quadruplex DNA in parallel and antiparallel G-quadruplex conformations24385152, similar to 1 – 3 treated Pu27 G4 (Figs S78–S80 and Table S10).…”
Section: Resultsmentioning
confidence: 85%
“…Comparison of the ESI-MS spectra before and after complex treated showed that 3 was coordinated to the guanine of G4-DNA (Fig. S77), whereas 6 and 10 might have been interacting with the π-π stacking of the G-quadruplex1033. FID and ESI-MS spectra experiments showed that the organometallic platinum(II) complexes 7 and 10 with a direct metal-carbon bond offers different possibilities for exploration as anticancer agents due to the large structural differentiation between the different ligands (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation